A Comparative Transcriptome Between Anti-drug Sensitive and Resistant Candida auris in China - Zhou, Wenkai; Li, Xiuzhen; Lin, Yiqing; Yan, Wei; Jiang, Shuling; Huang, Xiaotian; Yang, Xinglong; Qiao, Dan; Li, Na (Frontiers in Microbiology, 2021)
Candida auris emerged as a pathogenic species of fungus that causes severe and invasive outbreaks worldwide. The fungus exhibits high intrinsic resistance rates to various first-line antifungals, and the underlying molecular mechanism responsible for its multidrug resistance is still unclear. In this study, a transcriptomic analysis was performed between two C. auris isolates that exhibited different anti-drug patterns by RNA-sequencing, namely CX1 (anti-drug sensitive) and CX2 (resistant). Transcriptomic analysis results revealed 541 upregulated and 453 downregulated genes in the resistant C. auris strain compared with the susceptible strain. In addition, our findings highlight the presence of potential differentially expressed genes (DEGs), which may play a role in drug resistance, including genes involved in ergosterol and efflux pumps biosynthesis such as SNQ2, CDR4, ARB1, MDR1, MRR1, and ERG genes. We also found that Hsp related genes were upregulated for expression in the anti-drug-resistant strain. Biofilm formation and growth conditions were also compared between the two isolates. Our study provides novel clues for future studies in terms of understanding multidrug resistance mechanisms of C. auris strains.